AI-Augmented Decision Making: A Framework for Enterprise Workflow Transformation - Dilipkumar Devarahosahalli Jayaram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial Intelligence is fundamentally transforming how enterprises approach decision-making and workflow management. This article examines the emerging paradigm of AI-augmented decision platforms and their impact on enterprise operations. Through analysis of real-world implementations, including ServiceNow's Intelligence Platform, this article explores how organizations are leveraging AI to enhance human decision-making capabilities while automating routine workflows. This article demonstrates that successful AI-human collaboration frameworks can significantly improve operational efficiency, decision quality, and customer experience outcomes. This article presents an architectural framework for implementing AI-driven decision platforms, addressing key considerations around integration, scaling, and security. This article suggests that organizations adopting these platforms experience marked improvements in workflow optimization and service delivery personalization, though careful attention must be paid to change management and system governance. This article contributes to the growing body of research on enterprise AI adoption and provides practical insights for organizations looking to enhance their decision-making capabilities through AI integration.
Keywords: Platform Architecture; Enterprise Modularity; Digital Transformation; ServiceNow Ecosystem; Integration Framework